Prasugrel or ticagrelor in patients with acute coronary syndrome and diabetes: a propensity matched substudy of RENAMI. Issue 6 (September 2019) - Conrotto, Federico; Bertaina, Maurizio; Raposeiras-Roubin, Sergio; Kinnaird, Tim; Ariza-Solé, Albert; Manzano-Fernández, Sergio; Templin, Christian; Velicki, Lazar; Xanthopoulou, Ioanna; Cerrato, Enrico; Rognoni, Andrea; Boccuzzi, Giacomo; et al.
Introduction: The safety and efficacy of prasugrel and ticagrelor in patients with diabetes mellitus presenting with acute coronary syndrome and treated with percutaneous coronary intervention remain to be assessed. Methods: All diabetes patients admitted for acute coronary syndrome and enrolled in the REgistry of New Antiplatelets in patients with Myocardial Infarction (RENAMI) were compared before and after propensity score matching. Net adverse cardiovascular events (composite of death, stroke, myocardial infarction and BARC 3–5 bleedings) and major adverse cardiovascular events (composite of death, stroke and myocardial infarction) were the co-primary endpoints. Single components of primary endpoints were secondary endpoints. Results: Among 4424 patients enrolled in RENAMI, 462 and 862 diabetes patients treated with prasugrel and ticagrelor, respectively, were considered. After propensity score matching, 386 patients from each group were selected. At 19±5 months, major adverse cardiovascular events and net adverse cardiovascular events were similar in the prasugrel and ticagrelor groups (5.4% vs. 3.4%, P =0.16 and 6.7% vs. 4.1%, P =0.11, respectively). Ticagrelor was associated with a lower risk of death and BARC 2–5 bleeding when compared to prasugrel (2.8% vs. 0.8%, P =0.031 and 6.0% vs. 2.6%, P =0.02, respectively) and a clear but not significant trend for a reduction of BARC 3–5 bleeding (2.3% vs. 0.8%, P =0.08). There were no significant differences in myocardial infarction recurrence and stent thrombosis. Conclusion: Diabetes patients admitted for acute coronary syndrome seem to benefit equally in terms of major adverse cardiovascular events from ticagrelor or prasugrel use. Ticagrelor was associated with a significant reduction in all-cause death and bleedings, without differences in recurrent ischaemic events, which should be confirmed in dedicated randomised controlled trials.